2008
DOI: 10.1007/s10875-008-9235-y
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 Family of Cytokines in T Regulatory Cell Development and Homeostasis

Abstract: Thus, IL-2 provides importance signals for Treg cell development and for their homeostasis in peripheral immune tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 40 publications
0
66
0
1
Order By: Relevance
“…Furthermore, IL-2 influences cell survival, differentiation [1] and the formation of immune memory cells [1,9] and acts as a negative regulator of immune activation [8]. Recent studies showed that IL-2 played a critical role in the differentiation and survival of regulatory T cells, thereby ensuring their significance in the control of the immune response [10]. Cytokines effectively participate in the pathogenesis of several pathological conditions, such as cancer and metabolic, infectious, autoimmune and inflammatory diseases [11,12].…”
Section: Interleukin 2 and The Immune Responsementioning
confidence: 99%
“…Furthermore, IL-2 influences cell survival, differentiation [1] and the formation of immune memory cells [1,9] and acts as a negative regulator of immune activation [8]. Recent studies showed that IL-2 played a critical role in the differentiation and survival of regulatory T cells, thereby ensuring their significance in the control of the immune response [10]. Cytokines effectively participate in the pathogenesis of several pathological conditions, such as cancer and metabolic, infectious, autoimmune and inflammatory diseases [11,12].…”
Section: Interleukin 2 and The Immune Responsementioning
confidence: 99%
“…A major role for IL-2 signaling in differentiation of Treg cells is emphasized by diminished numbers of Foxp3 + cells in mice lacking IL-2 or IL-2Ra or IL2Rb chains, the latter shared by IL2 and IL15 receptors. Furthermore, a complete lack of Foxp3 + cells is found in mice lacking common g-chain (gc), a shared signaling subunit of all gc family cytokines, or three key members of the family, IL-2, IL-15, and IL-7 (Fontenot et al 2005b;Burchill et al 2007;Malek et al 2008;Vang et al 2008). Since STAT5 is a key transcription factor activated downstream from gc cytokine signaling, it was proposed that STAT5 plays a pivotal role in induction of Foxp3 expression.…”
Section: Regulation Of Foxp3 Expressionmentioning
confidence: 99%
“…Treg, making them highly dependent on exogenous IL-2 for their maintenance in the periphery [6, [14][15][16][17]. Deficiency of IL-2, CD25, or CD122 produces fatal autoimmune/inflammatory disease, which is mainly due to defective survival of natural Treg [23]. Yet, it is still conceivable that IL-2 nonproduction by Treg reduces in vitro Treg suppressive activity but, unlike CTLA-4, IL-2, CD25, or CD122 deficiency, fails to breach self-tolerance.…”
Section: Introductionmentioning
confidence: 99%